Einblicke in ein Referenzmodell zur Analyse der Einführung von Vektoren in Schulbüchern - Mai, Tobias; Biehler, Rolf (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Fachdidaktisches Design von Begründungsvideos im Projekt studiVEMINTvideos - Biehler, Rolf; Guntermann, Dominik; Liebendörfer, Michael; Krämer, Sandra; Schlüter, Sarah (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Das totale Differential und die Richtungsableitung – Eine Analyse mit Blick in ausgewählte Lehrbücher - Lankeit, Elisa; Biehler, Rolf (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Life, Theory, and Group Identity in Hannah Arendt's Thought, by Karen Fry - Robaszkiewicz, Maria Anna (Arendt Studies)
Keywords: Energy Engineering and Power Technology; Fuel Technology

Reclaiming the Public Space: Critical Phenomenology of Women’s Revolutions in Dark Times - Robaszkiewicz, Maria Anna (Journal of the British Society for Phenomenology)
Keywords: Philosophy

Entwicklung eines neuen Konzeptes zur Vermittlung von Lerntechniken und Selbstlernkompetenzen für Studierende des Maschinenbaus an der Universität Paderborn - Bentrup, Leon Alexander; Gräßer, Melanie; Temmen, Katrin; Schmid, Hans-Joachim (die hochschullehre)

Virtual Test Scenarios for Human-Centered Design with Virtual Measurement Systems - Gräßler, Iris; Roesmann, Daniel; Unverzagt, Marc; Pottebaum, Jens (Sensor and Measurement Science International (SMSI 2023))

Die Plattformisierung des Songwritings. Musik erfinden unter Bedingungen des short video turn am Beispiel von TikTok - Haenisch, Matthias; Godau, Marc; Barreiro, Julia; Maxelon, Dominik; Neuhausen, Timo (44. Jahresband des Arbeitskreises Musikpädagogische Forschung / 44th Yearbook of the German Association for Research in Music Education)

A new approach to model the fluid dynamics in sandwich packings - Franke, Patrick; Shabanilemraski, Iman; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny Y. (Chemical Product and Process Modeling)
Abstract Sandwich packings represent new separation column internals, with a potential to intensify mass transfer. They comprise two conventional structured packings with different specific geometrical surface areas. In this work, the complex fluid dynamics in sandwich packings is modeled using a novel approach based on a one-dimensional, steady momentum balance of the liquid and gas phases. The interactions between the three present phases (gas, liquid, and solid) are considered by closures incorporated into the momentum balance. The formulation of these closures is derived from two fluid-dynamic analogies for the film and froth flow patterns. The adjustable parameters in the closures are regressed for the film flow using dry pressure drop measurements and liquid hold-up data in trickle flow conditions. For the froth flow, the tuning parameters are fitted to overall pressure drop measurements and local liquid hold-up data acquired from ultra-fast X-ray tomography (UFXCT). The model predicts liquid hold-up and pressure drop data with an average relative deviation of 16.4 % and 19 %, respectively. Compared to previous fluid dynamic models for sandwich packings, the number of adjustable parameters could be reduced while maintaining comparable accuracy.
Keywords: Modeling and Simulation; General Chemical Engineering

Elektrooptischer Mischer - Kruse, Stephan; Scheytt, J. Christoph
Die Erfindung betrifft einen elektrooptischen Mischer (1) mit elektrischem Ausgang, aufweisend: • eine Photodiode (PD), • einen ersten Anschluss, • einen zweiten Anschluss, • wobei die Anschlüsse eine erste Spannungsversorgung (V1) und eine zweite Spannungsversorgung (V2) oder eine erste Stromversorgung (I1) und eine zweite Stromversorgung (I2) anschließbar ist, • einen Anschluss für ein Kleinsignal-Massepotential, • ein erstes Teilanpassungsnetzwerk (Z2, Z4), welches auf der Anodenseite der Photodiode (PD) angeordnet ist, wobei ein Teil des ersten Teilanpassungsnetzwerkes (Z2) mit dem Anschluss für die zweite Spannungsversorgung (V2) schaltbar (S2) verbindbar ist, und wobei ein anderer Teil des ersten Teilanpassungsnetzwerkes (Z4) mit dem Anschluss für das Kleinsignal-Massepotential schaltbar (S2') verbindbar ist, • ein zweites Teilanpassungsnetzwerk (Z1, Z3), welches auf der Kathodenseite der Photodiode (PD) angeordnet ist, wobei ein Teil des zweiten Teilanpassungsnetzwerkes (Z1) mit dem Anschluss für die erste Spannungsversorgung (V1) schaltbar (S1) verbindbar ist, und wobei ein anderer Teil des zweiten Teilanpassungsnetzwerkes (Z3) mit dem Anschluss für das Kleinsignal-Massepotential schaltbar (S1') verbindbar ist, • ein erstes entkoppelndes Element (C1) angeordnet auf der Kathodenseite und ein zweites entkoppelndes Element (C2) angeordnet auf der Anodenseite der Photodiode (PD), • wobei zwischen den von der Photodiode (PD) abgewandten Seiten des ersten entkoppelnden Elementes (C1) und des zweiten entkoppelnden Elementes (C2) im Betrieb einelektrisches Ausgangssignal bereitgestellt werden kann.

Analysis of Phase Noise in Waveguide-integrated Optical Test Structures in Silicon Photonics - Surendranath Shroff, Vijayalakshmi; Kress, Christian; Bahmanian, Meysam; Scheytt, J. Christoph (2023 PhotonIcs & Electromagnetics Research Symposium (PIERS),)
This paper experimentally investigates and interprets the e®ects of noise and non- linearity in a silicon photonic optical test structure. For the analysis di®erent optoelectronic phase noise measurement techniques are used. Our tests focuses on the performance of integrated opti- cal test structures using femtosecond pulses in the 1550nm spectral range. A primary objective is to understand the behaviour of silicon photonic waveguides that can be further employed in the implementation of an optoelectronic phase-locked loop (OEPLL) in silicon photonics technology. A comparison of our results, as well as a discussion on the di®erent optoelectronic phase noise measurement techniques are presented. Our ¯ndings provide insights that can be leveraged to optimize the design and performance of ultra-low phase noise on-chip OEPLL systems locking to mode-locked laser (MLL) signals. In the future such systems can be essential for advanced communication and sensing applications.

Methoden zur Förderung von Kompetenzen für eine demokratische Kultur - Schriftliche Reflexionen von Lehramtsstudierenden aus bildungswissenschaftlichen Seminaren - Wehde, Janis; Bloh, Bea

Der formelle Diskurs Forschenden Lernens in der Lehrerbildung. Ein Blick zurück nach vorn - Homt, Martina; Bloh, Bea (Lehrerbildung auf dem Prüfstand)

On Word Error Rate Definitions and Their Efficient Computation for Multi-Speaker Speech Recognition Systems - von Neumann, Thilo; Boeddeker, Christoph; Kinoshita, Keisuke; Delcroix, Marc; Haeb-Umbach, Reinhold (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
We propose a general framework to compute the word error rate (WER) of ASR systems that process recordings containing multiple speakers at their input and that produce multiple output word sequences (MIMO). Such ASR systems are typically required, e.g., for meeting transcription. We provide an efficient implementation based on a dynamic programming search in a multi-dimensional Levenshtein distance tensor under the constraint that a reference utterance must be matched consistently with one hypothesis output. This also results in an efficient implementation of the ORC WER which previously suffered from exponential complexity. We give an overview of commonly used WER definitions for multi-speaker scenarios and show that they are specializations of the above MIMO WER tuned to particular application scenarios. We conclude with a discussion of the pros and cons of the various WER definitions and a recommendation when to use which.
Keywords: Word Error Rate; Meeting Recognition; Levenshtein Distance

MeetEval: A Toolkit for Computation of Word Error Rates for Meeting Transcription Systems - von Neumann, Thilo; Boeddeker, Christoph; Delcroix, Marc; Haeb-Umbach, Reinhold (Proc. CHiME 2023 Workshop on Speech Processing in Everyday Environments)
MeetEval is an open-source toolkit to evaluate all kinds of meeting transcription systems. It provides a unified interface for the computation of commonly used Word Error Rates (WERs), specifically cpWER, ORC WER and MIMO WER along other WER definitions. We extend the cpWER computation by a temporal constraint to ensure that only words are identified as correct when the temporal alignment is plausible. This leads to a better quality of the matching of the hypothesis string to the reference string that more closely resembles the actual transcription quality, and a system is penalized if it provides poor time annotations. Since word-level timing information is often not available, we present a way to approximate exact word-level timings from segment-level timings (e.g., a sentence) and show that the approximation leads to a similar WER as a matching with exact word-level annotations. At the same time, the time constraint leads to a speedup of the matching algorithm, which outweighs the additional overhead caused by processing the time stamps.
Keywords: Speech Recognition; Word Error Rate; Meeting Transcription

Frame-Wise and Overlap-Robust Speaker Embeddings for Meeting Diarization - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

A Teacher-Student Approach for Extracting Informative Speaker Embeddings From Speech Mixtures - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (INTERSPEECH 2023)

Multi-stage diarization refinement for the CHiME-7 DASR scenario - Boeddeker, Christoph; Cord-Landwehr, Tobias; von Neumann, Thilo; Haeb-Umbach, Reinhold (7th International Workshop on Speech Processing in Everyday Environments (CHiME 2023))

Mixture Encoder for Joint Speech Separation and Recognition - Berger, Simon; Vieting, Peter; Boeddeker, Christoph; Schlüter, Ralf; Haeb-Umbach, Reinhold (INTERSPEECH 2023)

Analysis of polycarbonate degradation at melt/FeCr-alloy interfaces as a function of the alloy composition by means of combinatorial thin film chemistry - Theile-Rasche, Chantal; Meng, T.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (SN Applied Sciences)
Interfacial reactions at the polycarbonate (PC)/FeCr-alloy interface during melt contact were studied as function of the Fe:Cr ratio within the alloy. Thin Fe/Cr films with lateral composition gradients were deposited by magnetron sputtering; the analysis of the films was done with microscopy and X-ray photoelectron spectroscopy (XPS). The local interfacial polymeric film formation could be therefore directly correlated with the Fe:Cr ratio. The local thickness and structure of the formed polycarbonate residue was analyzed by means of imaging ellipsometry, atomic force microscopy as well as Fourier-transform infrared spectroscopy under grazing incidence and XPS. Moreover, confocal fluorescence microscopy of the PC melt/alloy interface could reveal the formation of minor degradation products in the interphase region. The results show that already an Fe:Cr ratio of 2 : 1 leads to a strong inhibition of the thermal degradation in comparison to the unalloyed iron, and that in general, the enrichment of chromium in the passive film leads to an effective suppression of interfacial PC degradation. The data contributes to improving the mechanistic understanding of the role of iron during this process. Additionally, a critical concentration of chromium in the alloys used for PC processing can be deduced.